Profiling elite/high performance sport athletes with impairments at selected South African universities - Mharakurwa, N.; Burnett, C.; Roux, C. J. (South African Journal for Research in Sport, Physical Education and Recreation, 2017)
Worldwide, universities have increasingly become hubs for high performance sports, as student-athletes enter the latter phase of the long-term athlete development process (LTAD). Within the South African context, several universities have and continue to play a significant role in the training and preparation of numerous participants for high level competition. This paper profiles the sport delivery practices for elite (high performance) AWI (Athletes with Impairments) across five South African universities. A descriptive, mixed-methods approach generated three data sets gathered through questionnaires, semi-structured interviews and document analysis. Data was captured from high performance AWI and top management of the university sports structures featuring AWI. Elite sport for AWI featured three different delivery models identified as `separate`, `integrated` and `hybrid` approaches. Of the five sampled institutions, only three have elite AWI totalling 30 athletes across 10 sport codes. Some of these institutions have successfully contributed to and supported elite AWI, who have excelled at provincial, national and international levels. Findings from this study also expose how AWI are still largely under-represented in elite sport across sampled institutions as reflected in the relatively low participation numbers